Newspaper coverage of human‐pig chimera research: A qualitative study on select media coverage of scientific breakthrough. (5th July 2017) - Hagan‐Brown, Abena; Favaretto, Maddalena; Borry, Pascal
Abstract: Background: A recently published article in the journal Cell by scientists from the Salk Institute highlighted the successful integration of stem cells from humans in pig embryos. This marks the first step toward the goal of growing human organs in animals for transplantation. There has, to date, been no research performed on the presentation of this breakthrough in the media. We thus assessed early newspaper coverage of the chimera study, looking into the descriptions as well as the benefits and concerns raised by the study mentioned by newspaper sources. Methods: We looked at newspaper coverage of the human‐pig chimera study in the two weeks after the publication of the article describing the breakthrough in Cell. This time period spanned from January 26 to February 9, 2017. We used the LexisNexis Academic database and identified articles using the search string "hybrid OR chimera AND pig OR human OR embryo." The relevant articles were analyzed using qualitative content analysis. Two researchers openly coded the articles independently using themes that emerged from the raw texts. Results: Our search yielded 31 unique articles, after extensive screening for relevance and duplicates. Through our analysis, we were able to identify several themes in a majority of the texts. Almost every article gave descriptive information about the chimera experiment with details about the study findings. All of the articles mentioned the benefits of the study, citing both immediate‐ and long‐term goals, which included creating transplantable human organs, disease and drug development, and personalized medicine, among others. Some of the articles highlighted some ethical, social, and health concerns that the study and its future implications pose. Many of the articles also offered reassurances over the concerns brought up by the experiment. Conclusions: Our results appeared to align with similar research performed on the media representation of sensitive scientific news coverage. We also explored the inconsistency between the tone of the titles and the articles that followed. However, it is still too early to speculate what impact the media will play in the public perception of this particular research.